Perancangan UI/UX Website Informasi Wisata Dan Penginapan Di Kabupaten OKUS Berbasis Mobile - Ibadi, Taqrim; Ramdhani, Muhammad Iqbal (Jurnal Ilmiah Matrik, 2024)
This research aims to design optimal user interface (UI) and user experience (UX) for a tourist and accommodation information website in OKUS District. Utilizing the Design Thinking approach with its five main stages: empathize, define, ideate, prototype, and test, the study is conducted to deeply understand user needs, clearly define problems, develop creative ideas, create solution prototypes, and test design iterations. The process begins with the empathize stage, where researchers seek to understand user experiences and needs thoroughly. Subsequently, the define stage is used to specify design problems and goals. The ideate stage involves the development of various creative solution ideas. Next, prototyping is used to transform ideas into tangible solutions for testing. Finally, the test stage is conducted to evaluate user responses to the prototype. The results of this research are expected to provide profound insights into designing a responsive tourist and accommodation information website catering to the needs of users in OKUS District. The conclusions drawn from this study include recommendations for implementing improved designs based on the findings from the Design Thinking method